Along‐strike continuity of structure, stratigraphy, and kinematic history in the Himalayan thrust belt: The view from Northeastern India. Issue 12 (22nd December 2016) - DeCelles, P. G.; Carrapa, B.; Gehrels, G. E.; Chakraborty, T.; Ghosh, P.
Abstract: The Himalaya consists of thrust sheets tectonically shingled together since ~58 Ma as India collided with and slid beneath Asia. Major Himalayan structures, including the South Tibetan Detachment (STD), Main Central Thrust (MCT), Lesser Himalayan Duplex (LHD), Main Boundary Thrust (MBT), and Main Frontal Thrust (MFT), persist along strike from northwestern India to Arunachal Pradesh near the eastern end of the orogenic belt. Previous work suggests significant basement involvement and a kinematic history unique to the Arunachal Himalaya. We present new geologic and geochronologic data to support a regional structural cross section and kinematic restoration of the Arunachal Himalaya. Large Paleoproterozoic orthogneiss bodies (Bomdila Gneiss) previously interpreted as Indian basement have ages of ~1774–1810 Ma, approximately 50 Ma younger than Lesser Himalayan strata into which their granitic protoliths intruded. Bomdila Gneiss is therefore part of the Lesser Himalayan cover sequence, and no evidence exists for basement involvement in the Arunachal Himalaya. Minimum shortening in rocks structurally beneath the STD is ~421 km. The MCT was active during the early Miocene; STD extension overlapped MCT shortening and continued until approximately 15–12 Ma; and growth of the LHD began ~11 Ma, followed by slip along the MBT (post‐7.5 Ma) and MFT (post‐1 Ma) systems. Earlier thrusting events involved long‐distance transport of strong, low‐taper thrust sheets, whereas events after 12–10 Ma stacked smaller, weaker thrust sheets into a steeply tapered orogenic wedge dominated by duplexing. A coeval kinematic transition is observed in other Himalayan regions, suggesting that orogenic wedge behavior was controlled by rock strength and erodibility. Key Points: Stratigraphy, shortening, and kinematic history of the Himalayan thrust belt are similar >1800 km along strike from NW to NE India Minimum shortening distance in rocks beneath the South Tibetan Detachment is 421 km Himalayan thrust belt experienced a major increase in orogenic wedge taper about 10–12 Ma